2019
DOI: 10.3390/ijerph16142601
|View full text |Cite
|
Sign up to set email alerts
|

The Actual Demand for the Elimination of Architectural Barriers among Senior Citizens in Poland

Abstract: The purpose of the study is to determine the actual demand for the elimination of architectural barriers among senior citizens in their place of residence and also in its immediate environment in Poland. The research covered a group of people in the post-productive age, living in the Lower Silesia voivodship in Poland. Different research methods were used in the study, primarily including the public opinion survey based on a questionnaire as well as statistical analyses. The cross-tabulation analysis of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…Therefore, the assessment could be incomplete and a lack of this data could represent a further limitation and necessity for the development of the model. The renewable energy applications by housing associations could also be relevant in other research, as in the context of energy poverty, vulnerable groups to energy poverty (impoverished people or ageing society) [28,62], spatial management [36], and comprehensive environmental management system [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the assessment could be incomplete and a lack of this data could represent a further limitation and necessity for the development of the model. The renewable energy applications by housing associations could also be relevant in other research, as in the context of energy poverty, vulnerable groups to energy poverty (impoverished people or ageing society) [28,62], spatial management [36], and comprehensive environmental management system [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The analyses carried out by Kurtyka-Marcak et al [12] and covering a similar group of respondents in terms of the demand for services in the immediate vicinity revealed that all the respondents, regardless of age and place of residence, indicated the need for a health centre in their close surroundings. The same was true for a grocery store (95% on average in each age group), a public transport stop (approx.…”
Section: Preferred Square Footage Of An Apartment/house and The Famentioning
confidence: 99%
“…The current state housing policy, addressed to senior citizens, allows adapting an apartment to age-related mobility limitations, as long as the person has a disability certificate. Activities focused on eliminating architectural barriers in seniors’ place of residence are particularly important in the context of improving their quality of life and independence [11,12]. The elderly, uncared for by their families, have nursing homes at their disposal in Poland, as long as they can afford to live in such institutions (i.e., receive a pension covering the costs of their stay).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the different 'players' in the field-the patients, clients, end-users, designers and formal and informal carers and other (allied) health professionals-and the physical, social, and digital environment is complex. This complexity, which is reflected in the differences in stakeholder needs, has its implications on the design of technology and buildings, as well as the environment around us [24][25][26][27][28][29]. Former research has shown that the relationship between human behaviour and the environment is not only country-, continent-, or culture-specific, but also age-, purpose-, and behaviour specific.…”
mentioning
confidence: 99%